Aksi Bersih Pantai Sebagai Upaya Menjaga Kebersihan Lingkungan Dikawasan Pantai Falajawa Kota Ternate - Unkhair, Firman; Yetty; Octasary, Magvirah; Widyawasti Anwar, Indry; Hi Muhammad, Hujaefa; Jusnita, Naniek (Jurnal Pengabdian Masyarakat Hutan, 2024)
Garbage is one of the problems faced by the people of Ternate City. One of solution to encourage people to care about the environment is by conducting socialization and beach clean-up activities. Thus, the lecturers of the English Language Education Study Program collaborated with the North Maluku Regional Police, students and the community conducted community service with the theme "Beach Cleaning Action as an Effort to Maintain Environmental Cleanliness in the Falajawa Beach, Ternate City". This activity aims to raise public awareness of environmental cleanliness and carry out clean-up activities in the Falajawa beach. This community service activity has been carried out well because of the support and cooperation between lecturers, students, North Maluku Regional Police and the Society. This activity began with conducting socialization about the importance of keeping the environment from rubbish, then continued with rubbish clean-up activities in the Falajawa Beach. By carrying out this community service activity through beach clean-up actions in the Falajawa Beach, it can raise public awareness of the importance of keeping the environment from rubbish, especially on the beach.